Dança e educação inclusiva: processos educacionais formativos de uma artista-professora-pesquisadora com deficiência auditiva na licenciatura em dança - TEIXEIRA, Ana Clara Lira (2023)
This research aims to carry out an analysis of the educational-artistic-formative processes for inclusive education from the autobiographical reports of an artist-teacher-researcher with hearing impairment under formation in the Faculty of Dance. It aims to bring the point of view from the experiences of a student with hearing impairment and her journey through the formal education processes and those of inclusion with especial attention to the role of the teacher in the educational institution, which are often not prepared to deal with students with deficiency. We consider in this work that the formation of a teacher is continuous, especially when it comes to the knowledge of the student’s deficiences, and that the formation processes are dependent on the knowledge of the reality from those who experience it. Thus, from my point of view, I intend to present the issue of hearing impairment and the process of inclusion of the deaf person in the formal education context from the perspective of a student-artist-teacher-in-training with hearing impairment. I defend the idea that a whole study of how to deal and create methodological strategies to work with people with disabilities is mandatory in the process of formation of teachers, which includes the knowledge about the routine of their students with deficiency outside the classroom and the school.